MINIMIZING RISK IN URBAN QUARRIES (Two Case Studies) - Wiliam Reisz; James Goldberg; Sally Zadra (International Society of Explosives Engineers, 2008)
Early recognition and risk assessment is critical to sustaining a safe and productive blasting operation. While every blasting environment holds inherent risk, highwall blasting in highly congested areas such as Hanson Material Service Corporation’s Romeoville and Thornton quarries in the greater south Chicago metropolitan area can be particularly perilous